(untitled) - Melissa Araújo Ulhoa; Nyam Florencio da Silva; José Guilherme Pinheiro Pires; Henrique de Azevedo Futuro Neto (Arquivos de Neuro-Psiquiatria)
In mammalian, several evidences suggest that central serotonin participates in thermoregulation. Nucleus raphe obscurus (NRO), a serotonergic nucleus, has been recognized to be the source of generation of various hemodynamic patterns in different behavioral conditions, but its involvement in thermoregulation is unclear. In the present study, extracellular action potentials of NRO neurons were recorded in anesthetized rats, which were submitted to cold and warm stimuli in the tail. The firing rate of the neurons was compared before and after each stimulation. It was found that 59% of the neurons submitted to a cold stimulus trial had a significant increase in their firing frequency, while 48% of the neurons submitted to warm stimulation trial were inhibited. The opposite responses in neuronal activity of NRO units to cooling or heating suggest that these cells are involved in producing the homoeothermic vascular adaptations secondary to changes in cutaneous temperature in the rat tail.